Feasibility of RF Sputtering and PIIID for production of thin films from red mud - Antunes, Maria Lúcia Pereira [UNESP] (2014)
During the extraction of aluminum from bauxite, a waste of oxides containing traces of heavy metals in a highly alkaline matrix, called Red Mud (RM), is produced. In this study RM is characterized and the feasibility of using it as a precursor for the production of thin films by Plasma Sputtering and by Plasma Immersion Ion Implantation and Deposition (PIIID) is demonstrated. The chemical structure and composition, surface morphology, topography, and wettability of the films prepared using such methodologies were investigated. The films consist mainly of the elements aluminum, silicon, iron and carbon. Infrared spectroscopic analyses reveal the presence of C=O, C-H2, Fe(OH), Al-O and Si-C functionalities. RF Sputtering produced films with smoother surfaces, whereas PIIID produced granular surface structures. Surface contact angle measurements showed that despite the presence of oxides and hydroxides, the films are hydrophobic, thus exhibiting an interesting link between the physical and thermodynamical properties.